Understanding Michael S. Harper - Antonucci, Michael (Michael A.) (Book collections on Project MUSE., 2023)
"A fresh examination of Harper's body of work as an archive of Black life, thought, and culture. The first book devoted to the groundbreaking poet's work, Understanding Michael S. Harper locates his poetic project within Black expressive tradition. The study examines poems drawn from the eleven volumes of verse that Harper (1938-2016) produced between 1970 and 2010, bringing attention to his poetry's sustained engagement with music, literature, and the visual arts. Michael A. Antonucci offers readers an account of the poet's career while assessing his verse and providing a sense of its perspective on Black America and the American experience. He develops and expands critical dialogues about the poet and his body of work, which, Antonucci argues, presents a counternarrative about the composition and origins of the United States, reshaping prevailing discourse about race, nation, and identity"--